If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + m = b Reorder the terms: m + r = b Solving m + r = b Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1r' to each side of the equation. m + r + -1r = b + -1r Combine like terms: r + -1r = 0 m + 0 = b + -1r m = b + -1r Simplifying m = b + -1r
| x^3-61=3 | | -4x^2+8x+11=0 | | 12t^2=27+27t | | .5x^2+2x-30=0 | | 10w^2-200=0 | | 8x+-2=6x | | 8x-2=6x | | w^2+11w-200=0 | | lnx=-4.833559 | | (8b^4-b^3)-(b^4+4b^3-4)= | | 4x^4+2x^3-108x-54=0 | | y^2+8x+16=0 | | x^3-9*x-1=0 | | y^2+6x+14y+43=0 | | 2y^2+14y+43=0 | | -16x^2+64x+128=0 | | -16x^2+64x+28=0 | | 8(-2x^2+8x+4)=0 | | 16x^2-25y^2+32x-100y+84=0 | | 0=x(5x+.5)-168 | | 32x^2-9x=0 | | 300=p(.03)(10) | | -16t^2+64x+32=0 | | 13r+1=3r-19 | | 6-24=48 | | 9x^2+2=10 | | 2x-3y+z=1 | | 9h+5=86 | | 5x-9=15-x | | 4x-2y+2z=6 | | 18x-(18x-6)=96 | | 7+(-3+-4y)=28 |